Active-site-directed inhibition of asparagine N-glycosyltransferases with epoxy-peptide derivatives. - Bause, E (1983)
The hexapeptide Arg-Asn-Gly-epoxyethylglycine-Ala-Val-OMe specifically inactivates membrane-bound N-glycosyltransferases. The specificity is demonstrated by the inability of peptides containing 2,3-epoxypropyl-, allyl- and vinyl-glycine in the epoxyethylglycine position to function as inhibitors. The inhibition is concentration-dependent and follows first-order kinetics, but requires disruption of the membrane vesicles by detergents to achieve accessibility to the transferase. The enzyme can be protected partially against inactivation by the addition of the acceptor peptide Arg-Asn-Gly-Thr-Ala-Val-OMe, pointing to an active-site-directed reaction. Exhaustion of the endogenous pool of glycosyl donor molecules by preincubation of the membrane vesicles with the acceptor peptide before inhibitor application is accompanied by an additional decrease in the inhibition rate. This suggests that inactivation occurs only under conditions where glycosyl transfer is catalysed. A mechanism of inactivation is proposed in which the transferase catalyses its own inactivation by a kind of 'suicide' mechanism.